Effects of microcredit and other loans on female empowerment in Bangladesh: the borrower's gender influences intra‐household resource allocation. (23rd February 2016) - Porter, Maria
Abstract: This article examines microcredit's effectiveness in empowering women borrowers in rural Bangladesh. It does so by examining how gender‐specific borrowing activities influence household expenditures which are either specifically of interest to men or women, and by examining the effects of all loans rather than only those provided by microcredit organizations. The article uses a quasi‐experimental design to identify the effects of borrowing by men and women by using an original combination of panel data and instrumental variables on subsamples of the surveyed population. It finds that the borrower's gender affects how households allocate their resources to different expenditure items and assets that are valued differently by men and women. In all, the findings suggest that providing greater credit access to women may improve their household bargaining positions.